Dynamics of occurrence of aquatic plants in the south-western part of the Silesian Upland (south Poland) - Urbisz, Andrzej; Urbisz, Alina (Biodiversity: Research and Conservation, 2006)
The study presents a listing of aquatic plants in the south-western part of the Silesian Upland and an estimation of the degree of threat to individual species, taking into account their present frequency of occurrence and dynamic tendencies in the study area. Among 73 analysed species, 10 are considered to be probably extinct in the study area, 33 are listed as rare or endangered (with a small or decreasing number of localities), while 30 are not threatened. 23 plant species are under legal protection, while 12 of them are listed in the “Polish Red Data Book of Plants”. The highest concentration of localities of aquatic plants was observed in the eastern part of the study area, in the vicinity of the town of Żory. Among the apparently extinct species, the majority are dicotyledonous plants, while monocotyledonous plants predominate in other two groups, which allows to draw the conclusion that they seem to be better adapted to anthropogenic transformations of the environment.